2017
DOI: 10.1016/j.taap.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Thiamine deficiency induces endoplasmic reticulum stress and oxidative stress in human neurons derived from induced pluripotent stem cells

Abstract: Thiamine (vitamin B1) deficiency (TD) plays a major role in the etiology of Wernicke's encephalopathy (WE) which is a severe neurological disorder. TD induces selective neuronal cell death, neuroinflammation, endoplasmic reticulum (ER) stress and oxidative stress in the brain which are commonly observed in many aging-related neurodegenerative diseases, such as Alzheimer's disease (AD), Parkinson's disease (PD), Huntington's disease (HD) and progressive supranuclear palsy (PSP). However, the underlying cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Our data reveal that ThDP may increase or decrease the viability of A549 cells in a p21-dependent manner, with the p53-p21 axes controlling the OGDHC response to cellular ThDP. In contrast, the viability of a normal epithelial cell line Vero is not reduced in the same concentration interval of ThDP, in good accord with the well-known antioxidant effects of the thiamine supplementation to non-cancer cells and tissues [33][34][35][36][37]. In the current work, we show that ThDP effects on viability of A549 cells depend on the functions of cellular OGDHC and p53-p21 pathway.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our data reveal that ThDP may increase or decrease the viability of A549 cells in a p21-dependent manner, with the p53-p21 axes controlling the OGDHC response to cellular ThDP. In contrast, the viability of a normal epithelial cell line Vero is not reduced in the same concentration interval of ThDP, in good accord with the well-known antioxidant effects of the thiamine supplementation to non-cancer cells and tissues [33][34][35][36][37]. In the current work, we show that ThDP effects on viability of A549 cells depend on the functions of cellular OGDHC and p53-p21 pathway.…”
Section: Introductionsupporting
confidence: 86%
“…A medically important contribution of the present work is the demonstration of a strong negative effect of a high dose of ThDP (known in medicine as cocarboxylase) on the viability of the adenocarcinoma epithelial cell line A549, which is not observed in a non-cancer epithelium cell line (Figure 6), nor acknowledged in any previous studies on the effects of ThDP and its precursor thiamine in a number of chemical [59,60] and biological systems [33][34][35][36][37]. After the incubation with 5 mM ThDP for 24 h, the viability impairment in A549 cells is manifested as a 70% decrease in cellular NAD(P)H:XTT reductase activity and 20-30% lower levels of cellular glutathione (Figure 6), accompanied by a 30% reduction of the glutathione redox potential (GSH/GSSG, Table 1) in A549 wt cells.…”
Section: Discussionmentioning
confidence: 54%
“…Some of the compounds we used to target these pathways (i.e. STF-083010 and KIRA8 against IRE1α and AEBSF against ATF6) have been extensively used in preclinical studies for neurodegenerative diseases, autoimmune diabetes, cancer and pulmonary fibrosis [46,65,[89][90][91][92][93]. Thus, simultaneous inhibition of IRE1α and ATF6 pathways using these drugs represents a promising antiviral strategy that could rapidly progress into a clinical trial.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Thus, going deeper into the pathogenesis of RNV and finding out an innovative therapy are extremely urgent at once. Salubrinal, a pharmacological inhibitor of eIF2α dephosphorylation, is known to possess a variety of biological effects, including anti-apoptosis [ 17 , 18 ], anti-arrhythmia [ 35 ], anti-thermal injury [ 36 ] and anti-oxidant [ 37 ]. Furthermore, some studies had reported the protective effect of salubrinal in hypoxic and ischemic diseases [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%